Gambaran Sarapan dan Status Gizi Pada Mahasiswa Fakultas Kedokteran Universitas Riau Angkatan 2017 - Isnani Kurniyanti; Erwin Christianto; Ismawati Ismawati (Fakultas Kedokteran Universitas Riau, 2018)
Breakfast is an activity of eating and drinking between waking up to 9 am to fulfill some of the daily nutritional needs (15-30% nutritional needs). The benefits of breakfast are maintaining an ideal body weight because breakfast can reduce the amount of food you eat throughout the day. The purpose of this study was to find out the description of breakfast and Body Mass Index (BMI) in students of the Faculty of Medicine, University of Riau in 2017. This research was descriptive study with 121 samples. The results showed 16.3% obese I and 8.1% obese II. Respondents with good breakfast calories tend to have good nutritional status of 50.0%.